Lomba Kreativitas Olahan Makanan Berbahan Dasar Porang bagi Ibu-Ibu PKK di Desa Karangpatihan, Kabupaten Ponorogo - Hudayana, Bambang; Triratnawati, Atik; Fauzanafi, Muhammad Zamzam; Yuniati, Eka; Fakhrani, Ferdy Azmal (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2024)
Abstract The creativity of the community in processing various types of porang-based foods is needed. Porang is a local Indonesian commodity that has enormous potential to be exported and sold in the international market. Porang tubers are the raw material for making shirataki rice which has a very high selling price. To achieve this goal, training in making processed food from porang is required. This community service programme focuses on training assistance in porang-based food processing. To see how much the community understands after receiving training, on the third day a porang-based food cooking competition was held to motivate residents to make new innovations related to porang food recipes that they develop. The target location for this community service programme is in Karangpatihan Village, Pulung District, Ponorogo Regency by targeting PKK mothers in four hamlets including Jurugan, Selodono, Krajan, and Dungus. This community service activity was closed with a focus group discussion (FGD) to listen to the aspirations of PKK women and see the future of porang in the region. As is the case in several other areas, the constraints of the community in processing porang are related to the processing of porang which is still quite complicated. In addition, the itchiness caused by holding porang in the hand.